Positive Emotions Program for Schizophrenia (PEPS): a pilot intervention to reduce anhedonia and apathy. Issue 1 (December 2015) - Favrod, Jérôme; Nguyen, Alexandra; Fankhauser, Caroline; Ismailaj, Alban; Hasler, Jean-David; Ringuet, Abel; Rexhaj, Shyhrete; Bonsack, Charles
Abstract Background Recent literature has distinguished the negative symptoms associated with a diminished capacity to experience (apathy, anhedonia) from symptoms associated with a limited capacity for expression (emotional blunting, alogia). The apathy-anhedonia syndrome tends to be associated with a poorer prognosis than the symptoms related to diminished expression. The efficacy of drug-based treatments and psychological interventions for these symptoms in schizophrenia remains limited. There is a clear clinical need for new treatments. Methods This pilot study tested the feasibility of a program to reduce anhedonia and apathy in schizophrenia and assessed its impact on 37 participants meeting the ICD-10 criteria for schizophrenia or schizoaffective disorders. Participants were pre- and post-tested using the Scale for the Assessment of Negative Symptoms (SANS) and the Calgary Depression Scale for Schizophrenia (CDSS). They took part in eight sessions of the Positive Emotions Program for Schizophrenia (PEPS)—an intervention that teaches participants skills to help overcome defeatist thinking and to increase the anticipation and maintenance of positive emotions. Results Thirty-one participants completed the program; those who dropped out did not differ from completers. Participation in the program was accompanied by statistically significant reductions in the total scores for Avolition-Apathy and Anhedonia-Asociality on the SANS, with moderate effect sizes. Furthermore, there was a statistically significant reduction of depression on the CDSS, with a large effect size. Emotional blunting and alogia remain stable during the intervention. Discussion Findings indicate that PEPS is both a feasible intervention and is associated with an apparently specific reduction of anhedonia and apathy. However, these findings are limited by the absence of control group and the fact that the rater was not blind to the treatment objectives. Conclusions PEPS is a promising intervention to improve anhedonia and apathy which need to be tested further in a controlled study. Trial registration number ISRCTN registryISRCTN74048461, registered 18 may 2015